Managing water and land at the interface between fresh and saline environments - McDonald, B. (2011)
The Bac Lieu Province in the Mekong Delta is part of the Cà Mau Peninsula and is an important foodgrowing area in Viet Nam. It has a population of 830,000 with approximately 116,000 farming families living on small parcels of land producing a range of commodities for food security and the export market. These farmers and aquaculturalists1 (together called producers in this report) are highly dependent on accessing the right quality water, fresh or saline or both, at the right time to grow their crops or raise their shrimp, crabs or fish. Water is delivered through an extensive network of canals and the intrusion of saline water into the area can be controlled on the southeastern side through the operation of sluice gates, a major investment in infrastructure undertaken by the Central Government of Viet Nam. In the early 2000s, there were conflicts over water use as shrimp aquaculturalists in particular began to see their supply of saline water being compromised. Also, many producers were living in poverty and in some areas inappropriate land use was leading to unsustainable futures. This project completed in 2007 and built on the work of two preceding projects2 is helping change that situation. What’s more, this impact will continue to grow as the outputs are more widely applied. 1 The term ‘aquaculturalist’ is used to differentiate people who ‘farm’ fish from those who catch fish in the wild. 2 The two projects are Accelerating Poverty Elimination through Sustainable Resource Management funded by DFID and Increasing Water Productivity by Managing Land-water Interface: Effective Water Control for Solving Conflicts among Agriculture-Fisheries-Aquaculture in Coastal Zones funded by CGIAR. With inputs including (i) approximately US$679,000 over 3 years, 86% from the Challenge Program on Water and Food (CPWF), (ii) support from CPWF in training in impact pathway analysis and for faceto- face meetings between the Bangladesh and Viet Nam components of this project to share experiences and lessons, (iii) an existing water management model ready for further development, (iv) the scientific knowledge of many local and international experts, (v) the experience of a wide range of partners in water management and production systems, (vi) the active participation of the provincial and local governments, (vii) the agreement of producers to provide their businesses as laboratories, (viii) the agreements of other producers to provide their farms as control farms with a likely opportunity cost, and (ix) the participation of producer groups who shared their experiences and insights, this project: • produced an improved Vietnamese River Systems and Plains (VRSAP) model that now contributes to improved sluice gate operations to better meet producers’ water needs; • used the model and other data to contribute to the development of the Bac Lieu People’s Committee’s Land Use Policy, which recognizes the benefits of diversification and the role of saline water in farming; and • developed and evaluated a successful participatory extension approach that assists producers select appropriate technologies (and reject others) based on on-farm demonstration and experimentation. On average, the demonstration site farms involved in the project made approximately US$250/ha/ year more than the controls (extrapolated from Ni et al. 2007). The producers interviewed believed the financial gain made a significant difference to their